Ad sanctos – de dödas plats under medeltiden - Andrén, Anders (Hikuin, 2000)
Ad sanctos – placing the dead in the Middle Ages By Anders Andrén Social analysis of graves is a recurring and problematic question in all kinds of archaeology. The question is also present in analyses of the often simple and uniform Christian graves from the Middle Ages. In contrast to pagan burials, in which social differences were mainly expressed through form and layout, it was above all the location of the grave that had social significance in the Christian Middle Ages. Normative sources like church laws clearly show that the fundamental principle in medieval burial customs was a principle of spatial closeness to holy spaces such as churches, altars, and relics. Ideas of closeness to the holy guided the principle of burial place in canon laws and Scandinavian church laws. According to Norwegian ecclesiastical laws the dead should be buried in different social zones in the churchyard, from slaves in the periphery to the king’s men by the church walls. Analyses of several almost completely excavated medieval cemeteries in Lund show that the normative principle of closeness to the holy functioned in practice, although the actual spatial setting changed successively through time. In the 11th century no burials took place inside the churches, except maybe in one case, but in the surrounding cemeteries the graves were placed in different zones. Wooden coffins on charcoal were placed around the church, whereas more simple graves without coffins and graves containing lepers were placed in the periphery, along the border of the churchyard. In the 12th and 13th centuries some people were buried in stone or brick tombs inside the churches, above all in the naves. Some dead were also buried in stone tombs placed close to the churches. The people buried in the tombs inside and outside the churches probably represented the urban elite of the 12th and 13th centuries. In the 14th, 15th and early 16th centuries the burial customs were more uniform. Above all a difference between burials inside and outside churches can be discerned. Besides, members of the elite were buried by altars in the cathedral, and some archbishops even had a special grave chapel erected by the cathedral. Thus, the access to the holy was successively expanded during the Middle Ages in Lund. Finally, it is important to stress that the principle of spatial closeness to the holy was a principle not only for placing the dead but also for placing the living. Access to the cemetery, the church and parts of the church was regulated by church laws and customs. The differentiated access was also stressed by the very layout, architecture and furnishing of the church. Thus, graves were part of a large spatial configuration of the church, and consequently should be analysed in relation to the church building and its adornment.